Phonon thermal transport and its tunability in GaN for near-junction thermal management of electronics: A review - Tang, Dao-Sheng; Cao, Bing-Yang (International journal of heat and mass transfer, 2023)
•Heat dissipation issues at near-junction region of GaN HEMT are reviewed comprehensively.•Phonon transport properties in GaN and GaN nanostructures are discussed based on both computations and experiments.•Phonon transport tuning mechanisms in perspectives of particle, wave, and topological nature of phonons for GaN and GaN nanostructures are introduced. The heat dissipation issue has now become one of the most important bottlenecks for power electronics due to the rapid increase in power density and working frequency. Towards the wide bandgap semiconductor GaN high electron mobility transistors (HEMTs), near-junction thermal management is the breakthrough that mainly includes the accurate thermal modeling and effective thermal design for GaN and GaN HEMTs. In this review, we first offer a comprehensive understanding of phonon thermal transport in GaN and GaN HEMTs, including non-equilibrium transport of electrons and phonons in the heat generation process, phonon thermal conductivity, heat spreading, and interfacial thermal transport. Then, we review the current tuning mechanisms and methods for thermal transport in GaN and GaN HEMTs which are classified into three categories according to the particle nature, wave nature, and topological nature of phonons. At last, we conclude by providing our perspectives on challenges and opportunities in the research of phonon thermal transport and its tuning mechanisms in GaN HEMTs.